Kajian Estetika Fotografi Karya Anton Ismael - Candra Prayogi (Journal of Science, Technology, and Visual Culture, 2023)
This research on photography focuses its study on photography by Anton Ismael which is compiled in the book Rumah Sesar, Sesat Dirumah, with the aims: (1) to describe the types of Anton Ismael's photography (2) to describe the aesthetic value in Anton Ismael's photographic work. This research is a qualitative descriptive study. Data collection techniques used are documentation, literature and triangulation techniques. The results showed that: (1) Anton Ismael's types of photography are: human life photography, art photography, mixed media photography and storytelling photography and (2) Anton Ismael's photography aesthetic values ​​are: visual elements (design elements) consisting of: six elements, namely: line, shape, texture, color, intensity/chroma, space and time; The basics of preparation (design principles) consist of four elements, namely, harmony blend, contrast blend, rhythm blend, and gradation blend; and the law of arrangement (design principle) consists of four elements, namely, the principle of unity, balance, simplicity (simplicity), accentuation (emphasis), and proportion.